2013
DOI: 10.1109/ted.2013.2238676
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Model for Organic Field-Effect Transistors With Improved Output Asymptotic Behaviors

Abstract: International audienceHere, we propose an advanced compact analytical current-voltage model for organic field-effect transistors (OFETs), which can be incorporated into SPICE-type circuit simulators. We improved the output saturation behavior by introducing a new asymptotic function that also enables more precise low-voltage current and conductance fitting. A new expression for the subthreshold current was suggested to cover all operation regimes of OFETs. All model parameters were extracted by a systematic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Iñiguez et al showed that an accurate OTFT compact model was able to be obtained by assuming only one exponential DOS with the variable range hopping theory and assumption of no free carriers [127]. The model has a similar formulation as the RPI one and allows to apply direct methods for parameter extraction, which is called a unified modelling and extraction method [128]. Bonnassieux and Horowitz et al implemented a more physical approach for OTFT compact modelling with Gaussian distribution of DOS for amorphous OSC and a power law for mobility and contact résistance [129].…”
Section: Statusmentioning
confidence: 99%
“…Iñiguez et al showed that an accurate OTFT compact model was able to be obtained by assuming only one exponential DOS with the variable range hopping theory and assumption of no free carriers [127]. The model has a similar formulation as the RPI one and allows to apply direct methods for parameter extraction, which is called a unified modelling and extraction method [128]. Bonnassieux and Horowitz et al implemented a more physical approach for OTFT compact modelling with Gaussian distribution of DOS for amorphous OSC and a power law for mobility and contact résistance [129].…”
Section: Statusmentioning
confidence: 99%
“…In addition, results of physical modelling can be used to improve the accuracy of compact models, which consist of simple mathematical descriptions of device behaviour needed for the simulation of integrated OFET circuits [12,13]. The rigorousness of compact modelling strongly relies on the input parameters such as the charge carrier mobility μ, contact resistance R c , and threshold voltage V T , which have usually been considered as constant fitting parameters [12][13][14][15]. Among them, V T is particularly important for OFETs because of the following reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, there are mainly two operational mechanisms of phototransistors, that is, photoconduction and photogating. Figure S5 schematically illustrates these two working modes, which were simulated with a compact model of n-type phototransistors. , For the photoconduction mode, the light intensity mainly affects the photoconductivity of the channel and modulates the off-state current, working more or less like a photoconductor without a gate. On the contrary, the light intensity mainly controls the threshold voltage in the photogating mode, and the incident light works as a virtual gate.…”
mentioning
confidence: 99%